Storia dei conventi cappuccini toscani dalla fondazione al 1704 La storia dell'Ordine da un manoscritto inedito di Filippo Bernardi da Firenze - Morozzi, Ubaldo (Biblioteca di storia, 2017)
This publication concerns the history of the Tuscan Capuchin convents since their foundation in the 18th century, analysed through the transcription and critical edition of a manuscript written in 1704 by Filippo Bernardi da Firenze (1649-1721). It is a source of great interest both for considering the events happening in the convents, and more generally for the history of Tuscany itself. In fact, the manuscript collects numerous transcribed documents - dating from the fifteenth to the eighteenth century - whose originals are now partially lost. Through these testimonies it is possible to retrace the events of the Tuscan communities and obtain numerous information of a social, anthropological and cultural nature. The manuscript is preceded by a historical introduction to the Order of Friars Minor Capuchin and by the biography of Filippo da Firenze.